1990
DOI: 10.1038/jcbfm.1990.17
|View full text |Cite
|
Sign up to set email alerts
|

PAF Antagonist Ginkgolide B Reduces Postischemic Neuronal Damage in Rat Brain Hippocampus

Abstract: Summary:We investigated the effect of the known an tagonist of platelet-activating factor (PAF), ginkgolide B, on postischemic neuronal damage in the rat. Neuronal necroses were evaluated in the hippocampus 7 days after a IO-min forebrain ischemia. Preischemic application of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(45 citation statements)
references
References 7 publications
2
43
0
Order By: Relevance
“…Preischemic administration of ginkgolide B (50 mg/kg) was found to significantly reduce neuronal necrosis at 7 days in a transient forebrain ischemia model in rats. 27 In the same model, Krieglstein et al 28 found that EGb (100/kg IV) given 45 minutes after ischemia was able to increase cerebral blood flow and diminish delayed hypoperfusion. EGb also produced beneficial effects on functional outcome in a cerebral microemboli model in rats 29 and in a global cerebral ischemia model in dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Preischemic administration of ginkgolide B (50 mg/kg) was found to significantly reduce neuronal necrosis at 7 days in a transient forebrain ischemia model in rats. 27 In the same model, Krieglstein et al 28 found that EGb (100/kg IV) given 45 minutes after ischemia was able to increase cerebral blood flow and diminish delayed hypoperfusion. EGb also produced beneficial effects on functional outcome in a cerebral microemboli model in rats 29 and in a global cerebral ischemia model in dogs.…”
Section: Discussionmentioning
confidence: 99%
“…EGb 761 also has anti-inflammatory effects and protective actions against brain damage through its terpenes and ginkgolides. 37,38 The ginkgolide B acts as an antagonist of PAF, 37 a factor that induces proinflammatory effects 39 and is activated in the HIV-infected brain. 40 Besides the free radical theory, inflammation is noted in the brains of HIV-infected individuals and of Tat transgenic mice.…”
Section: Neurotherapeutic Function Of Egb 761 Against Tat Neurotoxicitymentioning
confidence: 99%
“…Many of these actions have been studied in nonneural cells and are assumed to occur in the nervous system as well. Therefore, excessive PAF promotes neuronal damage, and PAFreceptor antagonists elicit neuroprotection in various models of neural injury (120,(133)(134)(135)(136)(137).…”
Section: Paf-mediated Cell Signal Transduction In the Nervous Systemmentioning
confidence: 99%